Analisis Habits of Mind Mahasiswa Pendidikan Biologi Berdasarkan 16 Indikator - Masiah Masiah; Siti Rabiatul Adawiyah; Lalu Jaswandi (Biocaster : Jurnal Kajian Biologi, 2026)
This study analyzes the habits of mind of biology education students based on 16 indicators from Costa and Kallick. The study used a descriptive quantitative approach with 22 purposively selected biology education students as subjects. Data were collected using a validated 4-point Likert scale questionnaire with high reliability (Cronbach's Alpha = 0.88). Data were then analyzed using descriptive statistics, the Friedman test, and Kendall's W test. The results showed that students' habits of mind were in the moderate category and uneven across all indicators. Persistence, empathy, thoroughness, and curiosity were in the high category, while flexible thinking was in the low category. The Friedman test showed significant differences between indicators with a moderate effect size (Kendall's W = 0.32). These findings demonstrate the need for biology learning designs that emphasize the development of flexible thinking through open inquiry, problem-based learning, and metacognitive reflection.